Um estudo sócio-linguístico da variação sintática ausência/presença de artigo definido diante de antropônimos na fala dos jovens de Barra Longa-MG que residem em Belo Horizonte - Ana Paula Mendes Alves (2008)
This study has taken the Variationist Sociolinguistics into account on analyzing the syntactic variation absence/presence of the definite article before anthroponyms - proper names of persons - in the speech of a young community from Barra Longa city, state of Minas Gerais, who lives in the capital of the state, Belo Horizonte. Despite being near to each other, the two cities have different patterns as to the variation studied. In the capital city the article is predominantly present (Moisés, 1995), whereas it is mostly absent in Barra Longa city (Mendes, 2000). After observing that the process of maintaining the article absence in this young community takes place in a variable way, the related linguistic and extralinguistic factors were investigated. Qualitative and quantitative analyses of the corpora were used in the present research. The two corpora comprised the speech data of twenty informants: the Belo Horizonte group was formed by sixteen informants from Barra Longa city, aged 18 to 30, living in Belo Horizonte city, and the control group was formed by four informants, living in Barra Longa city. 1163 data were obtained from the former group, and 340 from the latter. All data were separately treated by a quantitative analysis using the statistical program GOLDLVARB/VARBRUL (2001). The outcomes have indicated a syntactic function of the noun phrase in which the anthroponym is found as the only linguistic factor that is relevant to the phenomenon studied. As for extralinguistic variables, the level of intimacy between the speaker and the referent as well as the factors directly related to the informants social network were outstanding.